Images et société au début du xie siècle : le décor sculpté de Saint-Benoît-sur-Loire et Saint-Germain-des-Prés - Barbara Franzé (Bulletin du Centre d’Études Médiévales d’Auxerre)
The porch tower of Saint-Benoît-sur-Loire and the nave of Saint-Germain-des-Prés have a common history : both were raised in the years 1020-1030, by clerics close to the Capetian power. The analysis of the carved decorations of these two buildings, among the first known works of the Romanesque age, confirms the close links between the two protagonists, the ecclesiastical sponsors and the sovereign : they give to see and put forward a certain ideology, relative to the society and its organization. Formulated during the Carolingian period and still valid at the time the decorations were created, this ideology is based on a tripartite articulation of society, in which each order (oratores, bellatores, agricolantes) acts in complementarity in an eschatological perspective. This ideology also designates the ruling elites : the clerics and the king, dedicated to collaborate for a just governance. In Saint-Benoît-sur-Loire both powers are highly valued, inside the porch tower but also on the north façade, opposite the town. In Saint-Germain-des-Prés, in a double space shared by clerics and laymen, the prerogatives of each are characterized : to the first the management of the sacred and intermediation with the divine, to the sovereign the defense of Christianity. In the two examples studied, the ideological intentions pursued by the designers require the formulation of a new rhetoric, by the image. The ideological intentions pursued by the designers require the formulation of a new rhetoric, by the image. This enters into coherence and takes advantage of the metonymy now established between the ecclesial building, made of stones, and the Ecclesia, the community of the faithful.